Warm range margin of boreal bryophytes and lichens not directly limited by temperatures. (17th August 2021) - Greiser, Caroline; Ehrlén, Johan; Luoto, Miska; Meineri, Eric; Merinero, Sonia; Willman, Benny; Hylander, Kristoffer
Abstract: Species at their warm range margin are potentially threatened by higher temperatures, but may persist in microrefugia. Whether such microsites occur due to more suitable microclimate or due to lower biotic pressure from, for example competitive species, is still not fully resolved. We examined whether boreal bryophytes and lichens show signs of direct climate limitation, that is whether they perform better in cold and/or humid microclimates at their warm range margin. We transplanted a moss, a liverwort and a lichen to 58 boreal forest sites with different microclimates at the species' southern range margin in central Sweden. Species were grown in garden soil patches to control the effects of competitive exclusion and soil quality. We followed the transplanted species over three growing seasons (2016–2018) and modelled growth and vitality for each species as a function of subcanopy temperature, soil moisture, air humidity and forest type. In 2018, we also recorded the cover of other plants having recolonized the garden soil patches and modelled this potential future competition with the same environmental variables plus litter. Species performance increased with warmer temperatures, which was often conditional on high soil moisture, and at sites with more conifers. Soil moisture had a positive effect, especially on the moss in the last year 2018, when the growing season was exceptionally hot and dry. The lichen was mostly affected by gastropod grazing. Recolonization of other plants was also faster at warmer and moister sites. The results indicate that competition, herbivory, shading leaf litter and water scarcity might be more important than the direct effects of temperature for performance at the species' warm range margin. Synthesis . In a transplant experiment with three boreal understorey species, we did not find signs of direct temperature limitation towards the south. Forest microrefugia, that is habitats where these species could persist regional warming, may instead be sites with fewer competitors and enemies, and with sufficient moisture and more conifers in the overstorey. Abstract : In a transplant experiment with three boreal understorey species, we did not find signs of direct temperature limitation towards the south. Forest microrefugia, that is habitats where these species could persist regional warming, may instead be sites with fewer competitors and enemies, and with sufficient moisture and more conifers in the overstorey.